Prenatal diagnosis of tethered spinal cord associated with sacrococcygeal teratoma. Issue 8 (19th February 2016) - Sivrikoz, Tugba Sarac; Has, Recep; Esmer, Aytul Corbacioglu; Kalelioglu, Ibrahim; Yuksel, Atil; Taskin, Orhun Cig
ABSTRACT: Tethered spinal cord is mostly caused by myelomeningocele and lipomyelomeningocele, while dermal sinus tract, diastematomyelia, lipoma, tumor, thickened/tight filum terminale, spinal trauma, and spinal surgery are among the other causes. Prenatal diagnosis of tethered cord has been reported, and it is usually associated with neural tube defects. We present an atypical presentation of a tethered spinal cord, which was associated with a sacrococcygeal teratoma and was diagnosed in the 23rd week of pregnancy by ultrasonography. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44 :506–509, 2016